Effects of Minimally Invasive Versus Open Pancreatoduodenectomy on Short-Term Surgical Outcomes and Postoperative Nutritional and Immunological Statuses: A Single-Institution Propensity Score-Matched Study - Shinsei Yumoto, MD; Hiromitsu Hayashi, MD, PhD; Kosuke Mima, MD, PhD; Daisuke Ogawa, MD; Rumi Itoyama, MD, PhD; Yuki Kitano, MD, PhD; Shigeki Nakagawa, MD, PhD; Hirohisa Okabe, MD, PhD; Hideo Baba, MD, PhD (Annals of Surgery Open)
Objective:. To evaluate the feasibility and clinical impact of minimally invasive pancreatoduodenectomy (MIPD) versus open pancreatoduodenectomy (OPD) on postoperative nutritional and immunological indices. Background:. The surgical advantages of MIPD over OPD are controversial, and the postoperative nutritional and immunological statuses are unknown. Methods:. In total, 306 patients who underwent MIPD (n = 120) or OPD (n = 186) for periampullary tumors from April 2016 to February 2024 were analyzed. Surgical outcomes and postoperative nutritional and immunological indices (albumin, prognostic nutritional index [PNI], neutrophil-to-lymphocyte ratio [NLR], and platelet-to-lymphocyte ratio [PLR]) were examined by 1:1 propensity score matching (PSM) with well-matched background characteristics. Results:. PSM resulted in 2 balanced groups of 99 patients each. Compared with OPD, MIPD was significantly associated with less estimated blood loss (P < 0.0001), fewer intraoperative blood transfusions (P = 0.001), longer operative time, shorter postoperative hospital stay (P < 0.0001), fewer postoperative complications (P = 0.001) (especially clinically relevant postoperative pancreatic fistula [P = 0.018]), and a higher rate of textbook outcome achievement (70.7% vs 48.5%, P = 0.001). The number of dissected lymph nodes and the R0 resection rate did not differ between the 2 groups. In elective cases with textbook outcome achievement, the change rates of albumin, PNI, NLR, and PLR from before to after surgery were equivalent in both groups. Conclusions:. MIPD has several surgical advantages (excluding a prolonged operative time), and it enhances the achievement of textbook outcomes over OPD. However, the postoperative nutritional and immunological statuses are equivalent for both procedures.